Levels of community integration achieved by adults with disabilities post discharge from a specialised in-patient rehabilitation unit in the Western Cape - Gretschel, Dietlind (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPhil (Rehabilitation))--Stellenbosch University, 2016.